Reduced microtubule acetylation in cystic fibrosis epithelial cells - Rymut, Sharon M. (American Physiological Society, 2013)
Dysfunctional cystic fibrosis transmembrane conductance regulator (CFTR) leads to many cellular consequences, including perinuclear accumulation of free cholesterol due to impaired endosomal transport. The hypothesis being tested is that CF-related perinuclear cholesterol accumulation due to disrupted endocytic trafficking occurs as a result of reduced microtubule (MT) acetylation. Here, it is identified that acetylated-α-tubulin (Ac-tub) content is reduced by ∼40% compared with respective wild-type controls in both cultured CF cell models (IB3) and primary Cftr−/− mouse nasal epithelial tissue. Histone deacetylase 6 (HDAC6) has been shown to regulate MT acetylation, which provides reasonable grounds to test its impact on reduced Ac-tub content on CF cellular phenotypes. Inhibition of HDAC6, either through tubastatin treatment or HDAC6 knockdown in CF cells, increases Ac-tub content and results in redistributed free cholesterol and reduced stimulation of NF-κB activity. Mechanistically, endoplasmic reticulum stress, which is widely reported in CF and leads to aggresome formation, is identified as a regulator of MT acetylation. F508del CFTR correction with C18 in primary airway epithelial cells restores MT acetylation and cholesterol transport. A significant role for phosphatidyl inositol-3 kinase p110α is also identified as a regulator of MT acetylation.